2021
DOI: 10.5797/jnet.cr.2020-0047
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Cell Technique through Mesh of Pipeline Embolization Device: A Case Report

Abstract: We report a case of coil embolization using trans-cell technique through mesh of a pipeline embolization device (PED). Case Presentation: A 55-year-old female developed a left cavernous carotid aneurysm (CCA) with left abducens nerve palsy. The abducens nerve palsy improved gradually after PED deployment for the aneurysm. Sixty-nine days after the procedure, the patient suddenly presented with a severe headache, left abducens nerve palsy, left eyelid edema, and left pulsatile tinnitus. Digital subtraction angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…They also reported that during stent-assisted coil embolization for an aneurysm in the tip of the ICA, the trans-cell technique with Marathon was easy because Marathon had a small diameter. Sonobe et al reported that the small diameter of Marathon allowed the trans-cell technique to be used for ruptured case of intracavernous sinus carotid artery aneurysm after placement of a flow diverter [ 3 ]. Uyama et al reported that during stent-assisted coil embolization of the ICA-posterior communicating artery aneurysm, the small diameter of Marathon made it easier to pass through a stented posterior communicating artery and perform the trans-cell technique [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that during stent-assisted coil embolization for an aneurysm in the tip of the ICA, the trans-cell technique with Marathon was easy because Marathon had a small diameter. Sonobe et al reported that the small diameter of Marathon allowed the trans-cell technique to be used for ruptured case of intracavernous sinus carotid artery aneurysm after placement of a flow diverter [ 3 ]. Uyama et al reported that during stent-assisted coil embolization of the ICA-posterior communicating artery aneurysm, the small diameter of Marathon made it easier to pass through a stented posterior communicating artery and perform the trans-cell technique [ 5 ].…”
Section: Discussionmentioning
confidence: 99%